2015
DOI: 10.1093/rheumatology/kev102
|View full text |Cite
|
Sign up to set email alerts
|

Difference in the expression of IL-9 and IL-17 correlates with different histological pattern of vascular wall injury in giant cell arteritis

Abstract: Herein we provide the first evidence that distinct populations of potentially autoreactive T cells, expressing different cytokines (Th17 vs Th9), characterize patients with particular histological subsets of GCA and may thus contribute to the heterogeneity of tissue lesions observed in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 18 publications
2
72
0
Order By: Relevance
“…Although Th1 and Th17 cytokines were not significantly elevated in the serum in the present case, we consider that these cytokines might have been activated at inflamed local sites as described in a previous report (15).…”
Section: Discussionsupporting
confidence: 53%
“…Although Th1 and Th17 cytokines were not significantly elevated in the serum in the present case, we consider that these cytokines might have been activated at inflamed local sites as described in a previous report (15).…”
Section: Discussionsupporting
confidence: 53%
“…These pleiotropic functions are achieved through the differentiation of naive CD4 + T cells in effector and/or memory cells of specialized phenotypes such as TH1, Th2, Th9 and Th17 cells [74]. In particular, compared with control subjects, patients with GCA show a massive artery infiltration by IFN-Îł-secreting Th1 [75,76], IL-9-secreting Th9 [77] and IL-17-secreting Th17 lymphocytes [75][76][77]. IFN-Îł levels in the GCA arteries are correlated with neo-angiogenesis and the outgrowth of the hyperplastic intima [78].…”
Section: Cd4 + T Cells Play Central Roles In the Function Of The Immumentioning
confidence: 99%
“…Differently from IL-17, IL-9 was modified only marginally by glucocorticoids. This apparent IL-9 low sensitivity to glucocorticoid inhibition may indicate a potential role for Th9 cells in steroid-resistant GCA [20].…”
Section: Il-9 and Th9 Cells In Large-vessel Vasculitismentioning
confidence: 98%
“…Beyond the role in promoting the Th2 response, IL-33 has also been associated recently with the secretion of IL-9 by human CD4 1 T cells isolated from peripheral blood [58][59][60], apparently indicating a potential role of Th9 cells in the pathogenesis of GCA. Analysis of IL-9 and IL-17 expression in different histological subsets of GCA has demonstrated that a different immunological polarization characterizes different histological patterns of GCA [20]. The different expression of cytokines in different patterns of tissue pathology may be of immunological relevance.…”
Section: Il-9 and Th9 Cells In Large-vessel Vasculitismentioning
confidence: 99%
See 1 more Smart Citation